ANALISIS PEDAGOGI KRITIS PAULO FREIRE DI SEKOLAH FORMAL - Rizqi Sofiana; Jannatan Maulana Khasri; Dina Zahra Maharani (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This research aims to analyze and explore the implementation of Paulo Freire's critical pedagogy within the context of formal schooling, which is currently dominated by the